Digital Transformation and Climate ChangeAwareness: Mediated Impact on Financial Performance via Green Technology SMEs - Dinda Fatmah; Mirhamida Rahmah; Yusriyah Rahmah; Zakiyah Zulfa Rahmah; Karina Ananda Putri; Chamdan Purnama (International Journal of Islamic Business and Economics (IJIBEC), 2025)
This study investigates the direct and indirect effects of digital transformation and climate change awareness on SME financial performance, with green technology adoption serving as a mediating variable. Drawing from stakeholder theory and the resource-based view, this research addresses a key gap in understanding how digital and environmental initiatives interact within halal-oriented small businesses. Empirical data from 192 halal food SME owners and managers in East Java were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) across 32 indicators. Findings reveal that digital transformation significantly enhances both green technology adoption and financial performance, underscoring its strategic value in expanding market access and operational efficiency. While climate change awareness strongly encourages green technology adoption, it lacks a direct financial impact. Notably, green technology adoption shows a negative effect on financial performance, likely due to high initial costs and integration challenges. The study contributes to the literature by demonstrating the complex trade-offs between environmental innovation and profitability in emerging market SMEs. It suggests that digital strategies may serve as a bridge toward sustainability without undermining financial goals. Practical implications include the need for targeted government incentives and support mechanisms to offset green transition costs and bolster competitive resilience in halal food SMEs.